Ameliorative potential of L-ascorbic acid in bovine clinical mastitis - Ranjan, Rakesh; Swarup, D; Naresh, RAM; C, R (The Indian Journal of Animal Sciences, 2005)
The ameliorative effect of L-ascorbic acid on intramammary antibiotic therapy in bovine clinical mastitis was studied. A dairy herd of 225-250 lactating cows was screened For clinical and subclinical mastitis. Animals (42) with clinical mastitis. each with only 1 affected quarter, were selected and were randomly divided into 2 equal groups (groups A and B) for therapeutic trial. Animals of group A (n = 21) received intramammary antibiotic infusion (ampicillin sodium 75 mg and cloxacillin sodium 200 mg/infusion) alone till CMT reaction become zero or for the maximum period of 5 days treatment Animals of group B received intramuscular L-ascorbic acid injection @ 20 mg/kg , for 3 consecutive daysalong with the antibiotic therapy as given to group A. Evaluation of therapy was done on the basis of CMT scores and physical examination of udder and milk on days 3,5 and 7 of treatment. Higher recovery rate was noted in cows of group B (80.95%) than in group A (71.82%). Also, the average requirement of antibiotic infusions was lower in group B (3.43± 0.20) than in group A (3.90± 0.19). Recovery in group B animals were faster and the effect was more pronounced on day 3 of the trial. Results of the present trial suggested that L-ascorbic acid had ameliorative potential in bovine clinical mastitis and could be used with intramammary antibiotic therapy to improve the cure rate.